Mythology – archaic relics or an archetypal and universal source of constant renewal? : an exploration of the relationship between myth and archetype in the myth of Demeter and Persephone - Conradie, Catharina Maria (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MPhil (Ancient Studies)--University of Stellenbosch, 2007.